PENEGAKAN HUKUM SEBAGAI UPAYA MENINGKATKAN PENDAFTARAN DAN PENCATATAN KEKAYAAN INTELEKTUAL DI INDONESIA - Budiman Sinaga; Baru Tulus Obtain Siambaton; Adirman Budi Nduru (Magister Hukum Universitas HKBP Nommensen, 2020)
Currently, registration and registration of intellectual property in Indonesia are still deficient compared to other countries. Therefore, it is necessary to research the registration and recording of intellectual property that is still low and efforts to improve the registration and recording of intellectual property in Indonesia. This study wants to find out the cause of registration and recording of intellectual property so that the required data is secondary data and primary data. Therefore, this research used normative and sociological legal research methods together to be able to complement each other. Based on the results of the study can be concluded as follows. Registration and recording of intellectual property in Indonesia are still low because the public does not know much about registration and recording. Also, the public feels free to do registration and recording because the enforcement of intellectual property law is still low as law enforcement is still not firm in the event of piracy of intellectual property. Various efforts have been made to increase the registration and recording of intellectual property in Indonesia, among others, through the enforcement of intellectual property laws that are getting better and registration and recording of intellectual property that is getting easier and cheaper.